Does Participation in Global Value Chains Promote Economic Growth? Evidence from Malaysia - Jawad Jamal , Ameer; Z. Miklif, Huda (UMSurabaya Publishing, 2026)
Using qualitative and quantitative analyses of data on GVC membership and Malaysia's GDP from 2000 to 2022, this study examines what GVCs are, their importance to economic growth, and how they influence it. The underlying premise of this study is that GVC membership positively contributes to economic development. Did GVC membership influence Malaysia's economic development during the study period? To answer this question, this study uses the Autoregressive Distributed Lag (ARDL). The industrial sector contributes significantly to both local and foreign value added in exports, and participation in GVCs has a positive impact on Malaysia's economic growth during the study period. The impact of GVC participation on the industrial sector is reciprocal. Furthermore, linking local markets with foreign markets helps provide advanced intermediate raw materials and introduces modern production methods and technologies that enhance the competitiveness and productivity of local firms. GVCs also involve more firms through upstream and downstream linkages because they allow industries to specialize in certain parts of the production process rather than completing the entire process. This makes it easier for new firms to enter the market and be more competitive